2017
DOI: 10.1111/pace.13099
|View full text |Cite
|
Sign up to set email alerts
|

Substrate characteristics and ablation outcome of left atrial tachycardia in rheumatic mitral valve disease

Abstract: Left atrial AT can occur in RHD patients postmitral valve replacement. Catheter ablation is feasible with high acute success rate. The incidence of late development atrial fibrillation is considerable after successful ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 27 publications
(34 reference statements)
0
15
0
Order By: Relevance
“…The high acute success in suppressing ATs by CA was, however, associated with a great heterogeneity among studies. With the exception of two studies, 17,20 studies published after 2010 were associated with a greater acute success compared to older studies with concomitant significant abatement of heterogeneity. These data F I G U R E 4 Atrial fibrillation occurrence at follow-up after catheter ablation of complex atrial arrhythmias after mitral valve surgery.…”
Section: Acute Procedural Successmentioning
confidence: 84%
See 4 more Smart Citations
“…The high acute success in suppressing ATs by CA was, however, associated with a great heterogeneity among studies. With the exception of two studies, 17,20 studies published after 2010 were associated with a greater acute success compared to older studies with concomitant significant abatement of heterogeneity. These data F I G U R E 4 Atrial fibrillation occurrence at follow-up after catheter ablation of complex atrial arrhythmias after mitral valve surgery.…”
Section: Acute Procedural Successmentioning
confidence: 84%
“…Other main features of clinical studies are reported in Table 1. Of note, demographic characteristics (including age and sex) were available in 218 patients (96%) 14–20,22–27 . Left ventricular ejection fraction (LVEF) was available in 183 patients (81%) from eight studies (57%) 14–18,22,23,27 and left atrial anteroposterior diameter was available in 156 patients (69%) 15–19,22,23,26,27 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations